Potret Evaluasi Kebijakan Keterwakilan Perempuan Dalam Politik - Jumanah Jumanah; Arif Nugroho; Nazmah Nuraini; Rizki Alpian; Resti Mastia (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The phenomenon of gender equality is still a challenge in Indonesia, especially in the involvement of women in public and political activities. In the history of general elections in Indonesia, women are still considered the second choice in the world of politics. The form of women's conflict over men's power is inseparable from the patriarchal system that is unjust. Placing women as the shadow of men, patriarchal society from the start assumed that men were stronger than women both in personal, family, community and state life. Patriarchal culture and social values in Indonesia require women not to participate in politics or government. The government has attempted to increase women's participation by implementing Law Number 8 of 2012 concerning General Elections which regulates a minimum quota of 30% of women's representation in political parties. However, there are still several obstacles such as the low representation of women in public space, the lack of gender sensitivity in the commitment of political parties, as well as cultural constraints and religious interpretations that are gender biased and patriarchal. The method used in this study was obtained from literature study activities and data collection by conducting literature studies and reviewing related theories from the results of previous studies, using visualization vos viewer. Although the role and activities of women in public life are increasing, their involvement in political activities is still limited. The representation of women in political and decision-making institutions is still low and disproportionate. This is due to the patriarchal culture that is still strong and the view of society that considers women inappropriate to be involved in politics.